2020
DOI: 10.3174/ajnr.a6615
|View full text |Cite
|
Sign up to set email alerts
|

A Hemodynamic Mechanism Correlating with the Initiation of MCA Bifurcation Aneurysms

Abstract: BACKGROUND AND PURPOSE: Previous studies have reported that MCA bifurcation aneurysms usually emerge on inclined bifurcations; however, the reason is unclear. We designed this study to explore hemodynamic mechanisms that correlate with the initiation of MCA bifurcation aneurysms. MATERIALS AND METHODS: Fifty-four patients with unilateral MCA bifurcation aneurysms and 54 control patients were enrolled in this study after propensity score matching, and their clinical and CTA data were collected. We extracted the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…In a meta-analysis, Can et al concluded that an increase in WSS and GON may contribute to intracranial aneurysm formation, whereas low WSS was associated with its rupture ( 18 ). In another study, Huang et al found a negative correlation between WSS and aneurysm for middle cerebral artery (MCA) bifurcation aneurysm ( 19 ). However, unlike intracranial aneurysms ( 20 ), VAA models are less common and most of the studies applying CFD analysis to VAAs are single or series case reports.…”
Section: Discussionmentioning
confidence: 97%
“…In a meta-analysis, Can et al concluded that an increase in WSS and GON may contribute to intracranial aneurysm formation, whereas low WSS was associated with its rupture ( 18 ). In another study, Huang et al found a negative correlation between WSS and aneurysm for middle cerebral artery (MCA) bifurcation aneurysm ( 19 ). However, unlike intracranial aneurysms ( 20 ), VAA models are less common and most of the studies applying CFD analysis to VAAs are single or series case reports.…”
Section: Discussionmentioning
confidence: 97%
“…It represents a frictional force from blood ow tangential to the arterial lumen. Previous research has indicated a correlation between WSS and formation and rupture of aneurysms [24][25][26] . In this study, we discovered signi cantly higher mean WSS associated with rupture risk status of VADAs.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we enrolled patients with unilateral C7 segment (PCoA) aneurysms confirmed by computed tomography angiography (CTA) from December 2019 to July 2021 in the neurosurgery department of Xiangya Hospital Central South University. The exclusion criteria were as follows: 1) aneurysm associated with arteriovenous malformation or moyamoya disease; 2) dissecting aneurysm; 3) mycotic aneurysm; 4) recurrent aneurysm treated with surgical clipping or interventional embolization; 5) aneurysm > 10 mm, which may affect the morphology of the parent vessel; 6) severe carotid artery stenosis (> 70%, according to the North American Symptomatic Carotid Endarterectomy Trial method) and 7) treatment with mechanical thrombectomy in the setting of acute ischemic stroke [ 12 , 13 ]. The control subjects were people who underwent CTA screening and were confirmed to be without aneurysms during the same period.…”
Section: Methodsmentioning
confidence: 99%
“…The model was divided into 0.15 mm tetrahedral meshes with a 5-layer boundary layer mesh near the fluid boundaries. The blood flow was defined as a laminar and incompressible Newtonian fluid, with a density of 1050 kg/m 3 and viscosity of 0.0032 kg/(m*s) [ 12 ]. The inlet boundary of the model was defined as a pulsatile velocity inlet (Supplemental Method 1) [ 15 ].…”
Section: Methodsmentioning
confidence: 99%